2005
DOI: 10.1556/avet.53.2005.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-tocopherol on antioxidant enzyme activities and lipid peroxidation in rainbow trout (Oncorhynchus mykiss)

Abstract: In this study, the effect of α-tocopherol on the antioxidant capacity of rainbow trout (Oncorhynchus mykiss) was determined. For this purpose, activities of antioxidant enzymes such as catalase (CAT), peroxidase (POD) and glutathione reductase (GSSG-Rx) were investigated. Enzyme activities were measured at 0 (control), 1, 3 and 5 h after α-tocopherol injection. In addition, the levels of malondialdehyde (MDA) as a lipid peroxidation marker were determined in the erythrocytes. The results showed that α-tocopher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…When the extreme O 2 À occurs SOD reduces the amount of superoxide radicals (O 2 À ) by converting to oxygen (O 2 ) and hydrogen peroxide (H 2 O 2 ) [75][76][77] . CAT is primary enzymatic defence against H 2 O 2 generation 78,79 . GPx protects the tissues against free radicals by limiting lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…When the extreme O 2 À occurs SOD reduces the amount of superoxide radicals (O 2 À ) by converting to oxygen (O 2 ) and hydrogen peroxide (H 2 O 2 ) [75][76][77] . CAT is primary enzymatic defence against H 2 O 2 generation 78,79 . GPx protects the tissues against free radicals by limiting lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The results were expressed as Units per milligrams of protein tissue. CAT activity in muscle tissue was measured using spectrophotometric methods 29,30 . Results were expressed as units per grams of protein.…”
Section: Biochemical Assaysmentioning
confidence: 99%
“…In a recent study, it was demonstrated that dimethoxy-bromophenol derivatives incorporating cyclopropane moieties have shown picomolar inhibition against cytosolic CA I, II and tumor-associated CA IX, and XII 9 . The relationship between anti-oxidant molecules and CA isoenzyme inhibition is well established [56][57][58] . It is well known that bromophenol derivatives had some biological activities including anti-oxidant and radical scavenging 55 , acetylcholine esterase inhibition properties 55,59 .…”
Section: Resultsmentioning
confidence: 99%